Climate change and primary health care in Africa: A scoping review - Lokotola, C.L.; Mash, R.; Naidoo, K.; Mubangizi, V.; Mofolo, N.; Schwerdtle, P.N. (The Journal of Climate Change and Health, 2023)
Background: Climate change is one of the biggest threats to global health and primary healthcare (PHC) .In Africa, building climate resilient PHC is a challenge as there is little evidence to inform health systems and policy makers. Aim: To determine the extent of the literature on climate change and PHC in the African context and identify knowledge gaps. Methods: A scoping reviews systematically searched the published and grey literature (2010−2021) including six databases (Scopus, Pubmed, Cinahl, Africa Wide, Web of Science, and Open Grey) and research repositories from prominent African universities. A comprehensive search strategy and data extraction from included studies were used. Data were analyzed both quantitatively and qualitatively. Results: A total of 1242 studies were identified and 12 included. Most of the articles were published from 2016 onwards. Publications came from five countries, with South Africa and Ghana having more than one. Most studies were narrative reviews or descriptive studies, using qualitative interviews or surveys. PHC services in Africa will experience increasing challenges of malnutrition, infectious diseases, heat-related conditions, injuries, non-communicable diseases, mental health problems and migration. However, there is an absence of actual surveillance or monitoring data. Only one study focused on the use of renewable energy as a means of resilience and mitigation. There were no studies on health financing implications. Conclusion: The literature is accruing on climate change and health in the African context, but there is a lack of evidence on climate resilient PHC. Ten priority research questions were identified
Keywords: Climatechange; Primaryhealthcare; Mitigation; Adaptation; Resilience; Africa